Primary Empty Sella Syndrome: A Case Report - Hossain, Md Sanwar; Mumu, Mahbuba Ashrafi; PK, Md Moyenuddin (Anwer Khan Modern Medical College Journal, 2011)
Primary Empty Sella Syndrome (PES) is a relatively rare or uncommon developmental disease that develops spontaneously. It is characterized by herniation of subarachnoid space within the sella which is often associated with some degree of flattening of pituitary gland. Usually manifested by endocrine abnormalities, ocular abnormalities, rhinitis and intractable persistent headache. It is higher in obese females having multiple pregnancies. Here we report a case of empty sella syndrome in a 27 year old lady to aware the physicians to bear in mind a differential in patients having persistent intractable headache. Key words: Empty Sella Syndrome; Woman; Obesity; Intractable Headache DOI: 10.3329/akmmcj.v1i1.7456 Anwer Khan Modern Medical College Journal 2010; 1(1): 23-25